Foreign sales strategies of multinational enterprises - Jörn Kleinert; Farid Toubal (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2010)
The business literature has long recognized the importance of multinationals' distribution networks. The empirical analysis of distribution-oriented FDI has, however, received little attention which is at least partly due to the lack of appropriate data. We outline a slightly modified version of Helpman, Melitz, and Yeaple (2004) that explicitly models the possibility for a multinational firm to export through its wholesale trade affiliate in order to analyze multinational firms' choice between foreign production and foreign distribution. The subsequent empirical analysis uses different discrete choice models. We use alternative specifications and report estimation results for several sub-samples of multinational firms. We also consider more complex foreign sales strategies and correct for the sample selection bias that arises because we only observe firms that have foreign affiliates. Our results show that the decision between distribution and production-oriented FDI is based on the trade-off between fixed and variable costs.
urn:nbn:de:bsz:21-opus-46849
Keywords: F23; F12; C25; 330; Multinational firms; Wholesale sales; Discrete choice; Multinationales Unternehmen; Internationale Markteintrittsstrategie; Direktinvestition; Exporthandel; Diskrete Entscheidung; Schätzung; Deutschland